The role of electrolyte and polyelectrolyte on the adsorption of the anionic surfactant, sodium dodecylbenzenesulfonate, at the air-water interface - Zhang, X; Taylor, D; Thomas, R; Penfold, J (2011)
The role of the polyelectrolyte, poly(ethyleneimine), PEI, and the electrolytes NaCl and CaCl2, on the adsorption of the anionic surfactant, sodium dodecylbenzenesulfonate, LAS, at the air-water interface have been investigated by neutron reflectivity and surface tension. The surface tension data for the PEI/LAS mixtures are substantially affected by pH and the addition of electrolyte, and are consistent with a strong adsorption of surface polymer/surfactant complexes down to relatively low surfactant concentrations. The effects are most pronounced at high pH, and this is confirmed by the adsorption data obtained directly from neutron reflectivity. However, the effects of the addition of PEI and electrolyte on the LAS adsorption are not as pronounced as previously reported for PEI/SDS mixtures. This is attributed primarily to the steric hindrance of the LAS phenyl group resulting in a reduction in the ion-dipole attraction between the LAS sulfonate and amine groups that dominates the interaction at high pH. © 2011 Elsevier Inc.